An exploration of women’s perspectives on their experiences of a multiple pregnancy - Holberton, Alice (2013)
Background In research and policy to date, there is an overwhelming focus on the potentially negative aspects and complications of multiple pregnancy. Although National Institute for Health and Clinical Excellence (NICE) guidelines identify that additional psychological support may be required by women expecting twins or triplets, there is currently a relative lack of qualitative research that seeks to identify the varying forms of support women desire during their pregnancies and beyond. Existing research tends to focus on physical risks and mental illness; little is said about developing more positive support and enhancing mental health promotion. In light of the omissions in research to date, this study sought to examine women’s perspectives on their experience of multiple pregnancy. Specifically, the study aimed to identify the factors women saw as both helpful and challenging during pregnancy. Women’s perspectives on the support they received and their suggestions for future healthcare provisions were also elicited. Methods Nine in-depth individual interviews were conducted with women attending multiples mother and baby groups in Nottinghamshire. A thematic analysis was conducted to highlight key themes emerging from women’s accounts. Findings Key findings highlighted women’s need for additional antenatal support, specifically relating to how best to physically manage with multiple infants. In addition, women highlighted the significance of the (lack of) support from health-care professionals. Positive sources of support for these women were found in their relationships with other women who had mutual understanding and experience of multiples – highlighting the value attached to the notion of empathy as a key aspect of their well-being. Implications Findings from this study point to a number of implications for health-care professionals, particularly with regards to the provision of empathetic support during the antenatal period. The study also offers new insights into these women’s experiences that may help inform future mental health promotion efforts for women expecting multiples.